(untitled) (Fourth World Journal, 2010)
This article advocates for women leading Emotional Climate Change by integrating culture, water, and consciousness to empower communities in health and education. It presents a case study called “the water story,” linking new scientific and consciousness research with traditional Indigenous knowledge, particularly from the Embera-Wounaan peoples in Panama. The article explores shifting focus from physical climate change to an emotional climate change, emphasizing the need to reconnect with nature. It highlights how this shift can foster community empowerment and healing, both in Indigenous jungles of Panama and inner-city neighborhoods of New Orleans. The study underscores the vital role of women in leading this transformation and the potential benefits for sustainable development and community well-being.